2019
DOI: 10.1111/ggi.13764
|View full text |Cite
|
Sign up to set email alerts
|

Increase in direct social care costs of Alzheimer's disease in Japan depending on dementia severity

Abstract: Aim With the aging population, costs of direct social support for patients with Alzheimer's disease have grown and will continue to increase. The purpose of the present study was to estimate the cost of direct social support for Alzheimer's disease under long‐term care insurance in Japan. Methods This cross‐sectional study included 169 patients with Alzheimer's disease or mild cognitive impairment who visited a memory clinic and were followed over time. Dementia severity, use of care services and costs were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The number of people with dementia has increased in East Asia and these areas, including Japan, face a great burden and need further studies to guide medical and non‐medical interventions 1 . Dementia occurs along a disease state continuum between mild and severe; many people with severe dementia have a strong onset of behavioural and psychological symptoms of dementia and are often institutionalised or hospitalised to treat the psychiatric symptoms 2 . Moreover, they have much higher care costs and care burdens than people with mild dementia 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of people with dementia has increased in East Asia and these areas, including Japan, face a great burden and need further studies to guide medical and non‐medical interventions 1 . Dementia occurs along a disease state continuum between mild and severe; many people with severe dementia have a strong onset of behavioural and psychological symptoms of dementia and are often institutionalised or hospitalised to treat the psychiatric symptoms 2 . Moreover, they have much higher care costs and care burdens than people with mild dementia 3 …”
Section: Introductionmentioning
confidence: 99%
“…1 Dementia occurs along a disease state continuum between mild and severe; many people with severe dementia have a strong onset of behavioural and psychological symptoms of dementia and are often institutionalised or hospitalised to treat the psychiatric symptoms. 2 Moreover, they have much higher care costs and care burdens than people with mild dementia. 3 Therefore, it is necessary to rehabilitate the patient according to the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from six countries reported on direct medical costs, which varied from $531 (China) to $1473 (USA), €171 (Spain) to €313 (France and Spain), £365 (UK), and JPY 26,744 (Japan) [ 6 , 44 , 63 65 , 81 , 85 ]. Finally, direct non-medical costs (i.e., social care costs such as home health assistance, community care, skilled nursing facility care, consumables), reported in five countries, were €141 to €589 (Spain), €1398 (meta-analysis of France and Spain), £975 (UK), $258 (China), and JPY 69,179 to JPY 81,970 (Japan) [ 6 , 44 , 63 65 , 81 , 86 ]. Among studies reporting on direct medical and non-medical costs, three studies and a meta-analysis reported that non-medical costs were higher (£975 vs. £365 in a UK study, €589 vs. €289 in a Spanish study, JPY 69,179 vs. JPY 26,744 in a Japanese study, and €1398 vs. €313 in a meta-analysis), whereas two studies reported that direct medical costs were higher than non-medical costs (€171 vs. €141 in another Spanish study and $1055 vs. $424 in a Chinese study).…”
Section: Resultsmentioning
confidence: 99%
“…Dependence level and cognitive decline have been associated with direct costs [ 70 , 73 75 , 81 , 86 ]. Studies conducted in France, Spain, Japan, the UK, and the USA found that as the level of functional dependence increased, direct costs also rose [ 70 , 73 75 , 81 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation